Social media- friend or foe? - Mwila, Mutale (School of Economics, 2024)
The use of social media has become a part of our daily lives. Thus, there is growing concern over social media platforms' impact on individuals and society. Beginning with an introductory chapter outlining research objectives, subsequent sections delve into various facets: Chapter two delineates the methodology and theoretical framework applied in this thesis. Chapter three scrutinises how the architecture of social media platforms exploits human vulnerabilities, leading to pervasive societal and individual harm. Chapter four explores social media's influence on collective well-being, encompassing its role in elections, global conflict, and information dissemination through major digital platforms. Chapter five investigates the psychological effects of social media on individuals, focusing on diverse literature and its impact on children's development. Moreover, this thesis evaluates proposed regulatory measures for governing social media platforms, assessing their practicality. Concluding remarks address limitations and suggest avenues for future research. By synthesising a wide array of perspectives, this thesis offers a comprehensive exploration of social media's implications, shedding light on its profound effects on societal dynamics and individual wellbeing.